PWE-141 A Positive Complement Dependent Cytotoxic (cdc) Crossmatch Does Not Impact On Patient Survival Or Increase The Risk Of Acute Cellular Rejection, Or Biliary Strictures After Liver Transplantation. (9th June 2014) - Dyson, J; Carter, V; Hudson, M; Manas, DM; Masson, S
Abstract : Introduction: The impact of donor specific antibodies on outcomes after liver transplantation remains controversial. We aimed to evaluate the impact of a positive lymphocyte complement dependent cytotoxic (CDC) crossmatch on patient survival and the incidence of complications following liver transplantation (LT). Methods: We analysed the outcomes for all patients undergoing LT in our centre over a 6 year period (January 2007–December 2012). All patients transplanted at our centre receive a retrospective CDC crossmatch. We examined the indication for transplantation, patient survival, complications (acute cellular rejection, biliary strictures, chronic ductopaenic rejection) and whether the complications correlated to the presence of a positive crossmatch pre- and post-treatment with dithiothreitol (DTT) for IgM/IgG or IgG antibodies. Results: There were 194 liver transplants performed in this period (60% male). A crossmatch was available for 186 patients. The median age of the recipients was 55 years (range 19–71 years). The primary indications for LT were alcoholic liver disease 31%, autoimmune liver disease 18%, hepatocellular carcinoma 11%, viral hepatitis 9%, vascular 7.5%, paracetamol toxicity 7.5%, NAFLD 5% and other 11%. There were 12 deaths (6.5%) in the time period studied. 76 patients had a positive crossmatch and of these 13 were IgG positive (i.e., positive post-DTT treatment). Patient survival did not correlate with the presence of an IgM or IgG positive crossmatch (Fisher's exact test, p = 1.000 for both). Acute cellular rejection (ACR) requiring augmentation of immunosuppression occurred in 38 patients (20%). Neither a positive IgM crossmatch (Chi-square test, p = 0.094) or a positive IgG crossmatch (Fisher's exact test, p = 1.000) correlated with the incidence of ACR. Clinically significant biliary strictures occurred in 14 patients (7.5%). The presence of a positive crossmatch did not correlate with the incidence of strictures (Chi square test, p = 0.124 for IgM antibodies and Fisher's exact test, p = 1.000 for IgG antibodies). Only 1 patient developed chronic ductopaenic rejection in our cohort. Conclusion: The presence of antibodies to donor lymphocytes (detectable by the CDC crossmatch) does not affect patient survival or the incidence of acute cellular rejection and biliary anastomotic strictures. Disclosure of Interest: None Declared.